2023
DOI: 10.3390/pathogens12020193
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms Involved in the Fluoroquinolone Resistance of Salmonella enterica Strains Isolated from Humans in Poland, 2018–2019: The Prediction of Antimicrobial Genes by In Silico Whole-Genome Sequencing

Abstract: Salmonellosis remains the second most common zoonosis in Europe. Resistance to fluoroquinolones (FQs) in Salmonella has been increasing worldwide, with WHO considering FQ-resistant Salmonella spp. as high-priority pathogens. The aim of this study was a retrospective analysis of the molecular mechanisms of FQ resistance, detected among clinical ciprofloxacin-resistant Salmonella enterica belonging to the most common serotypes. The whole genome sequences (WGS) of tested isolates were also analysed for the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Fluoroquinolones and broad-spectrum cephalosporins are now the recommended antimicrobial medicines for the treatment of MDR S. typhi due to the development of resistance to traditional antibiotics ( Veeraraghavan et al ., 2018 ). However, research suggests that cases of typhoidal Salmonella are becoming increasingly resistant to fluoroquinolones ( Piekarska et al ., 2023 ). S. paratyphi exhibits more fluoroquinolone resistance than S. typhi in nations with a higher prevalence of MDR isolates ( Kumar et al ., 2017 ).…”
Section: Nomenclaturementioning
confidence: 99%
“…Fluoroquinolones and broad-spectrum cephalosporins are now the recommended antimicrobial medicines for the treatment of MDR S. typhi due to the development of resistance to traditional antibiotics ( Veeraraghavan et al ., 2018 ). However, research suggests that cases of typhoidal Salmonella are becoming increasingly resistant to fluoroquinolones ( Piekarska et al ., 2023 ). S. paratyphi exhibits more fluoroquinolone resistance than S. typhi in nations with a higher prevalence of MDR isolates ( Kumar et al ., 2017 ).…”
Section: Nomenclaturementioning
confidence: 99%
“…OqxAB encoded by the PMQR oqxAB gene is a novel transmissible resistance-nodulation-division (RND) efflux pump that can remove a wide range of antibiotics from bacterial cells (Wong et al, 2014). Whole-genome sequencing revealed that in addition to QRDR and PMQR, the quinoloneresistant Salmonella Typhi had mutations in an additional 19 genes, including tet, sul, aad, aac-, ant-, aph-, floR and cmlA (Piekarska et al, 2023). The AcrAB-TolC efflux pump was an important resistance factor to levofloxacin in the fluoroquinolone-resistant MDR isolates of S. Typhi and Paratyphi A (Okanda et al, 2018).…”
Section: Mechanisms Of Extensively Drug-resistance (Xdr)mentioning
confidence: 99%
“…Fluoroquinolones, such as ciprofloxacin, are the recommended drugs for treatment of severe Salmonella infections in humans (Li et al, 2018). However, the prevalence of ciprofloxacin resistance in non-typhoidal Salmonella isolates has increased in several countries, including Thailand (Utrarachkij et al, 2017;Sriyapai et al, 2021;Hengkrawit et al, 2022;Piekarska et al, 2023). With an increasing global trend of ciprofloxacin resistant Salmonella, WHO has announced this resistant bacterium as an urgent threat to public health (WHO, 2019).…”
Section: Introductionmentioning
confidence: 99%